2013
DOI: 10.1016/j.resp.2013.07.007
|View full text |Cite
|
Sign up to set email alerts
|

l-Cysteine ethyl ester reverses the deleterious effects of morphine on, arterial blood–gas chemistry in tracheotomized rats

Abstract: Summary This study determined whether the membrane-permeable ventilatory stimulant, L-cysteine ethylester (L-CYSee), reversed the deleterious actions of morphine on arterial blood-gas chemistry in isoflurane-anesthetized rats. Morphine (2 mg/kg, i.v.) elicited sustained decreases in arterial blood pH, pO2 and sO2, and increases in pCO2 (all responses indicative of hypoventilation) and Alveolar-arterial gradient (indicative of ventilation-perfusion mismatch). Injections of L-CYSee (100 μmol/kg, i.v.) reversed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
52
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(58 citation statements)
references
References 87 publications
6
52
0
Order By: Relevance
“…L-Cys and their derivatives are often used as biological models due to the remarkable thiol group that can be found in different oxidation states, and thus dictating the biological function of the proteins. For example, the functional derivative of L-Cys, L-Cysteine ethyl ester (L-CysEE), has many applications in chemistry, biochemistry, food sciences, and biomedical research [1][2][3][4]. L-CysEE has been used in the chemical synthesis of the majority of nonsteroidal anti-inflammatory drugs (NSAIDs) due to the presence of the SH functional group (to confer antioxidant properties) and the presence of the natural amino acid scaffold (for reduced toxicity) [1].…”
Section: Introductionmentioning
confidence: 99%
“…L-Cys and their derivatives are often used as biological models due to the remarkable thiol group that can be found in different oxidation states, and thus dictating the biological function of the proteins. For example, the functional derivative of L-Cys, L-Cysteine ethyl ester (L-CysEE), has many applications in chemistry, biochemistry, food sciences, and biomedical research [1][2][3][4]. L-CysEE has been used in the chemical synthesis of the majority of nonsteroidal anti-inflammatory drugs (NSAIDs) due to the presence of the SH functional group (to confer antioxidant properties) and the presence of the natural amino acid scaffold (for reduced toxicity) [1].…”
Section: Introductionmentioning
confidence: 99%
“…This quotient can be affected by numerous factors (e.g., changes in T B , hypoxia as elicited by opioids) that directly or indirectly affect metabolic rate and carbohydrate and lipid metabolism (see Mendoza et al, 2013). A switch to carbohydrate metabolism would increase RQ whereas a switch to lipid metabolism would decrease RQ (see Mendoza et al, 2013; van Klinken et al, 2013). The minor changes in BT observed in this study would minimally affect RQ.…”
Section: Discussionmentioning
confidence: 99%
“…), did not alter glucose, lactate or high-energy metabolite levels in the brains of rats (Keykhah et al, 1988), (3) intra-coronary fentanyl produced minor effects on left-ventricular mechanoenergetics in dog hearts over a wide range of blood concentration (Kohno et al, 1997), and (4) fentanyl was devoid of major effects on myocardial metabolism in isolated rat hearts (Blaise et al, 1990). Although several studies have provided evidence that morphine can either enhance or decrease lipid metabolism (see Mendoza et al, 2013). There is little direct evidence as to the effects of fentanyl on lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…11 Later, a high dose Nacetyl cysteine (NAC) was shown to increase minute ventilation in humans. 13 Our lead compound, D-cystine diME, safely reversed OIRD without affecting analgesia in two rodent models. We previously showed that L-Cysteine ethyl ester reversed negative effects of morphine in tracheotomized rats.…”
mentioning
confidence: 91%
“…We previously showed that L-Cysteine ethyl ester reversed negative effects of morphine in tracheotomized rats. 13 Our lead compound, D-cystine diME, safely reversed OIRD without affecting analgesia in two rodent models. 14 Remarkably, D-cystine diME did not have the cystinosis-like toxicities of the L-cystine esters 15,16 or the cardiovascular effects of extracellularly delivered (intravascular) S-nitrosothiols.…”
mentioning
confidence: 91%